Hematologic, immunologic reconstitution, and outcome of 342 autologous peripheral blood stem cell transplantations after cryopreservation in a −80°C mechanical freezer and preserved less than 6 months. Issue 3 (15th July 2012) - Calvet, Laure; Cabrespine, Aurélie; Boiret‐Dupré, Nathalie; Merlin, Etienne; Paillard, Catherine; Berger, Marc; Bay, Jacques‐Olivier; Tournilhac, Olivier; Halle, Pascale
<x xml:space="preserve">Abstract</x> BACKGROUND: Controlled‐rate freezing and storage in nitrogen is the standard technique for cryopreservation of peripheral hematopoietic progenitor cells (PHPCs) but presents high cost and dimethyl sulfoxide (DMSO) toxicity. Cryopreservation at −80°C, by uncontrolled rate freezing with only 3.5% DMSO, preserves the functional capacities of PHPCs, produces successful engraftment, and reduces toxicity during infusion. STUDY DESIGN AND METHODS: Long‐term hematopoietic and immunologic reconstitution for 342 autografts (311 adults, 31 children) after PHPCs were cryopreserved at −80°C was studied at 3, 6, and 12 months. The median (range) storage time of PHPCs cryopreserved was 1.7 (0.1‐5.99) months. RESULTS: Hemoglobin (Hb), white blood cells, and platelets (PLTs) reach normal values to trilineage at 12 months for 39% patients. Multivariate analysis shows a significant impact on CD34+ infused and on conditioning regimen for PLTs. Hb was influenced by growth factor administration at 3 months. Long‐term recovery is also highly dependent on blood counts (Hb, PLT, and neutrophil) at start of high‐dose chemotherapy. Only 43% of patients had reached normal lymphocyte values at 12 months after transplant, and a profound CD4+ T‐lymphocyte deficit remained, as others reported. CONCLUSION: Transplantation with PHPCs cryopreserved at −80°C for no more than 6 months is satisfactory for long‐term hematopoietic and immunologic reconstitution, even if a profound CD4+ T lymphocyte deficit persists at 1 year. This easier and cheaper cryopreservation method also leads to successful engraftment.